1994
DOI: 10.1007/bf00686668
|View full text |Cite
|
Sign up to set email alerts
|

New development of transarterial immunoembolization (TIE) for therapy of hepatocellular carcinoma with intrahepatic metastases

Abstract: The prognosis of patients with multiple hepatocellular carcinoma (HCC) remains disappointing. In this study, we devised a new therapeutic modality for HCC consisting of transarterial immunoembolization (TIE) using OK-432 and fibrinogen and then analyzed the preliminary results. In the first series, we applied the treatment to 19 patients with advanced HCC who had proved to be insensitive to several previous conventional treatments. In all, 14 patients (74%) with unresected HCC have currently survived for betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“… 28 Kanai et al reported that transarterial immunoembolization with OK‐432 and fibrinogen was effective, but caused fever in 100% of the patients treated. 29 If OK‐Lipo is used in place of unencapsulated OK‐432, systemic side effects, such as fever, will be lessened because there is little extravasation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Kanai et al reported that transarterial immunoembolization with OK‐432 and fibrinogen was effective, but caused fever in 100% of the patients treated. 29 If OK‐Lipo is used in place of unencapsulated OK‐432, systemic side effects, such as fever, will be lessened because there is little extravasation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…OK432, a penicillin-killed and lyophilized preparation of a low-virulence strain of Streptococcus pyogenes that was developed by Okamoto et al, is successfully used as an immunotherapeutic agent in malignancies by polarizing the T-cell response to a helper T-cell 1 (Th1)dominant state [16][17][18] . Preliminary studies have shown that transarterial immunoembolization (TIE), in which a mixture of OK-432, fibrinogen, and thrombin is injected into the hepatic artery before clotting via a catheter introduced by the Seldinger technique, has a tumoricidal effect against hepatocellular carcinoma 19,20) . In these reports, the beneficial effects of TIE were evident not only for inoperable patients but also for patients with resectable tumors as a preoperative therapy 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mitomycin can eliminate the suppressor cells or suppressor factor in the blood or effusion, resulting in augmented anticancer activity of OK-432-activated immunopotentiating cells, especially T-cells [31,32]. It was also proven by histological examination that transarterial immunoembolization (TIE) seems to be more effective than conventional TAE for the therapy of extracapsular invasion and prevention of intrahepatic metastases in humans [14,33]. Okuno et al found that hepatic infusion of IL-2 can increase the permeability of the hepatic endothelium, resulting in an increase of hepatic extraction of antitumor agents [34].…”
Section: Discussionmentioning
confidence: 98%